Basic Nahwu Learning Problems at MTs Al-Irsyad East Cape Jabung - M. Riadi Saputra; M. Syukron Maksum (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze the problems of basic nahwu learning in students of MTs Al-Irsyad Tanjung Jabung Timur and the efforts of teachers in overcoming them. Nahwu as one of the important branches of learning Arabic is often considered a difficult, abstract, and boring material by students. These difficulties have an impact on the low understanding of Arabic sentence structure and weak ability to read Arabic texts. This study uses a mixed method approach with qualitative dominance through a sequential exploratory design. The research subjects consisted of 2 Arabic teachers, 1 madrasah head, and 48 grade VIII students. Data collection techniques use observation, interviews, learning difficulty questionnaires, documentation, and diagnostic tests. Data analysis is carried out through data reduction, data presentation, conclusion drawn, and quantitative descriptive statistical strengthening. The results of the study show that the main problems of basic nahwu learning include low mastery of mufradat, weak understanding of the concept of i’rab, learning methods that are still teacher-centered, lack of learning media, and low student learning motivation. The average score of students’ understanding of nahwu only reached 61.8 from the minimum completeness standard of 75. The novelty of this research lies in the analysis of basic nahwu problems based on the context of rural madrasas with limited learning resources and solution approaches through the integration of contextual examples of student life. This study recommends the application of nahwu learning that is more communicative, simple, and contextual so that students can more easily understand the structure of the Arabic language. Abstrak Penelitian ini bertujuan untuk menganalisis problematika pembelajaran nahwu dasar pada siswa MTs Al-Irsyad Tanjung Jabung Timur serta upaya guru dalam mengatasinya. Nahwu sebagai salah satu cabang penting dalam pembelajaran Bahasa Arab sering dianggap sebagai materi yang sulit, abstrak, dan membosankan oleh siswa. Kesulitan tersebut berdampak pada rendahnya pemahaman struktur kalimat Arab serta lemahnya kemampuan membaca teks berbahasa Arab. Penelitian ini menggunakan pendekatan mixed method dengan dominasi kualitatif melalui desain sequential exploratory. Subjek penelitian terdiri atas 2 guru Bahasa Arab, 1 kepala madrasah, dan 48 siswa kelas VIII. Teknik pengumpulan data menggunakan observasi, wawancara, angket kesulitan belajar, dokumentasi, dan tes diagnostik. Analisis data dilakukan melalui reduksi data, penyajian data, penarikan kesimpulan, serta penguatan statistik deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa problematika utama pembelajaran nahwu dasar meliputi rendahnya penguasaan mufradat, lemahnya pemahaman konsep i’rab, metode pembelajaran yang masih berpusat pada guru, minimnya media pembelajaran, serta rendahnya motivasi belajar siswa. Nilai rata-rata pemahaman nahwu siswa hanya mencapai 61,8 dari standar ketuntasan minimum 75. Novelty penelitian ini terletak pada analisis problematika nahwu dasar berbasis konteks madrasah pedesaan dengan keterbatasan sumber belajar serta pendekatan solusi melalui integrasi contoh kontekstual kehidupan siswa. Penelitian ini merekomendasikan penerapan pembelajaran nahwu yang lebih komunikatif, sederhana, dan kontekstual agar siswa lebih mudah memahami struktur Bahasa Arab.